PENGARUH DEBT TO EQUITY RATIO, RETURN ON EQUITY DAN EARNING PER SHARE TERHADAP HARGA SAHAM PADA PT AKASHA WIRA INTERNATIONAL TBK PERIODE 2015-2024 - Jeni Rosianti; Fakung Rahman (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
Abstract. This study aims to analyze the effect of Debt to Equity Ratio, Return on Equity, and Earning Per Share on stock prices of PT Akasha Wira International Tbk for the period 2015–2024. This research uses a quantitative approach with secondary data obtained from the company’s financial statements. The analytical methods used include classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination test using SPSS version 26. The results show that partially DER and ROE do not have a significant effect on stock prices, while EPS has a positive and significant effect on stock prices. Simultaneously, Debt to Equity Ratio, Return on Equity, and Earning Per Share have a significant effect on stock prices with an F-value of 26.642 > F-table 4.76 and a significance value of 0.001< 0.05. The Adjusted R Square value of 0.895 indicates that 89.5% of the variation in stock prices can be explained by these variables, while the remaining 10.5% is influenced by other variables not examined in this study. Keywords: Debt to Equity Ratio, Return on Equity, Earning Per Share, Stock Price